Effect of workplace physical activity interventions on the cardio-metabolic health of working adults: systematic review and meta-analysis - Rubina Mulchandani; Ambalam M. Chandrasekaran; Roopa Shivashankar; Dimple Kondal; Anurag Agrawal; Jeemon Panniyammakal; Nikhil Tandon; Dorairaj Prabhakaran; Meenakshi Sharma; Shifalika Goenka (BMC, 2019)
Abstract Background Adults in urban areas spend almost 77% of their waking time being inactive at workplaces, which leaves little time for physical activity. The aim of this systematic review and meta-analysis was to synthesize evidence for the effect of workplace physical activity interventions on the cardio-metabolic health markers (body weight, waist circumference, body mass index (BMI), blood pressure, lipids and blood glucose) among working adults. Methods All experimental studies up to March 2018, reporting cardio-metabolic worksite intervention outcomes among adult employees were identified from PUBMED, EMBASE, COCHRANE CENTRAL, CINAHL and PsycINFO. The Cochrane Risk of Bias tool was used to assess bias in studies. All studies were assessed qualitatively and meta-analysis was done where possible. Forest plots were generated for pooled estimates of each study outcome. Results A total of 33 studies met the eligibility criteria and 24 were included in the meta-analysis. Multi-component workplace interventions significantly reduced body weight (16 studies; mean diff: − 2.61 kg, 95% CI: − 3.89 to − 1.33) BMI (19 studies, mean diff: − 0.42 kg/m2, 95% CI: − 0.69 to − 0.15) and waist circumference (13 studies; mean diff: − 1.92 cm, 95% CI: − 3.25 to − 0.60). Reduction in blood pressure, lipids and blood glucose was not statistically significant. Conclusions Workplace interventions significantly reduced body weight, BMI and waist circumference. Non-significant results for biochemical markers could be due to them being secondary outcomes in most studies. Intervention acceptability and adherence, follow-up duration and exploring non-RCT designs are factors that need attention in future research. Prospero registration number: CRD42018094436.